Autoimmune GFAP astrocytopathy manifesting as sintilimab-induced myelitis: a Case Report and literature review - Ma, Xue; Qin, Xing (Frontiers in Immunology, 2025)
Immune checkpoint inhibitors (ICIs) targeting programmed cell death protein 1 (PD-1), programmed cell death protein 1 ligand, and cytotoxic T-lymphocyte-associated protein 4, are important therapeutic approaches for malignancies. However, these novel treatment measures are associated with immune-related adverse events. We report the first reported case of autoimmune GFAP astrocytopathy-associated myelitis in a patient with hepatocellular carcinoma that was treated with sintilimab (an anti-PD-1 monoclonal antibody) immunotherapy. Additionally, literature review identified 21 previously reported cases of PD-1 inhibitor-associated myelitis, demonstrating similar clinical features. All patients received ICI discontinuation and high-dose glucocorticoid therapy, with the addition of other immune therapies in 15 patients. Clinical improvement was observed in 13 patients. Clinicians should consider autoimmune GFAP astrocytopathy-associated myelitis as a potential differential diagnosis among patients exhibiting neurological symptoms during or following ICI therapy.